The impact of mindfulness practice on physician burnout: A scoping review - Malik, Hani; Annabi, Carrie Amani (Frontiers in Psychology, 2022)
Background Physician burnout is a growing phenomenon in current health systems worldwide. With the emergence of COVID-19, burnout in healthcare is progressively becoming a serious concern. Increasing emotional exhaustion, depersonalization, and reduced personal accomplishment threaten the effective delivery of healthcare. Compassion fatigue and moral injury are a considerable risk to the doctor-patient relationship. These issues can potentially be mitigated by mindfulness practice, which has shown promising results in reducing burnout, restoring compassion, and preventing moral injury in physicians. Methodology A scoping review was conducted to investigate the effects of mindfulness practice on physician burnout. High-ranking journals were targeted to analyze high-quality studies and synthesize common themes in the literature. Studies conducted on current practicing physicians were included. Mindfulness practice of varying forms was the main intervention studied. Gray literature and studies conducted only on allied health personnel were excluded from this review. Results 31 studies were included in this scoping review. Mindfulness practice decreased emotional exhaustion and depersonalization while improving mood, responses to stress, and vigor. Self-awareness, compassion, and empathy were also increased in study participants. From this review, four themes emerged: innovations in mindfulness practice, mindfulness and positive psychology, the impact of mindfulness on work and patient care, and barriers and facilitators to physician mindfulness practice. Conclusion Mindfulness was widely reported to benefit mental health and well-being, but the studies reviewed seemed to adopt a mono focus and omitted key considerations to healthcare leadership, systems-level culture, and practices. Mindfulness practice is a quintessential component of positive psychology and is inherently linked to effective leadership. A mindful and compassionate physician leader will play a crucial role in addressing current practice gaps, prioritizing staff mental health, and providing a supportive platform for innovation.